ANALISIS PENERIMAAN PAJAK DAN PERTUMBUHAN EKONOMI DI INDONESIA - Basia, Lusmino; Umabaihi, Widya Anggita (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to analyze the effect of tax revenue on the growth of the country's economy in Indonesia. The background of this study is that there are several things that affect the instability of economic growth, one of which is tax revenue. When economic growth continues to decline, it can be said that economic development is not running and experiencing Therefore, the importance of tax revenue as a source of state revenue with efforts to increase taxes will have a major impact on the Indonesian economy because it can be used to finance development for the welfare of the people and various government programs. The research method used is secondary data obtained from BPS, World Bank, and the Ministry of Finance of the Republic of Indonesia in 1988-2022, and obtained using eviews-12 software. The results of the study show that tax revenue does not have a significant effect on Indonesia's economic growth in both the short and long term. Based on these findings, it is recommended that the government continue to improve efficiency in tax management and expand the tax base to support sustainable economic growth.